“Baldatun Tayyibatun Wa Rabbul Ghafur”: The Foundation of a Nation Wellbeing - Abdullah, Mohd Farid Ravi; Nasir, Mohd Norzi; Usman, Abur Hamdi (International Journal of Psychosocial Rehabilitation, 2020)
The Baldatun Tayyibatun wa Rabbul Ghafur nation is a form of Islamic model that is clearly stated in the Quran. The model is based on the conception of Islamic principle, that adopts Islamic order preservation approach, and executes nation development based on the guidelines embodied in the Quran and Sunnah. Therefore, this working paper will explicate the features of Baldatun Tayyibatun wa Rabbul Ghafur as the basis of global Islamic nation building. By understanding the Baldatun Tayyibatun principle and its features, the greatness of a nation civilisation will reinstate. Thus, the basic of a nation’s wellbeing relies on its political stability, holistic education system, fair economic system and sustainable environment.